Promise unfulfilled : unions, immigration and the farm workers - Martin, Philip L., 1949- (Cornell University Press, 2003)
In 1975, after vigorous campaigning by the United Farm Workers union, the state of California passed the Agricultural Labor Relations Act (ALRA), a pioneering self-help strategy granting farm workers the right to organize into unions. A quarter century later, only a tiny percentage of farm workers in the state belong to unions, and wages remain less than half of those of nonfarm employees. Why did the ALRA fail? One of the nation's foremost authorities on farm workers here explores the reasons behind its unfulfilled promise. Philip L. Martin examines the key features of the farm labor market in California, including the shifting ethnicity of the worker pool and the evolution of the major unions, beginning with the Wobblies. Finally, he reviews the impact of immigration on agriculture in the state. Today, many states look to the California experience to assess whether the ALRA can serve as a model for their own farm labor relations laws. In Martin's view, California's efforts to grant rights to farm workers so that they can help themselves have failed because of continued unauthorized migration and the changing structure of farm employment. Martin argues that alternative policies would make farming profitable, raise farm worker wages, and still keep groceries affordable.